The world of cooperative enterprise - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
The world of cooperative enterprise 1995 256pp price UKL 16.95 ISBN 0 85042 175 6 The Plunkett Foundation, 23 Hanborough Business Park, Long Hanborough Oxford OX8 8LH, UK